Measuring regional competitiveness: A survey of approaches, measurement and data - Gábor Békés (Hungarian Academy of Sciences, Institute of Economics, 2015)
This paper reviews a set of issues related to the concept and measurement of regional competitiveness. First, the concept of growth and competitiveness is argued to be different at regional level from the national level. In particular, the relationship between agglomeration and performance, the role of FDI in regions, and the key aspect of local institutions are analyzed. Second, a detailed review is carried out on potential data sources to gauge regional competitiveness using official, private sector as well as academic datasets.
Keywords: R11; R38; 330; regional competitiveness; data audit